2006
DOI: 10.1523/jneurosci.1882-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Panoramic Measurements of the Apex of the Cochlea

Abstract: Our understanding of cochlear mechanics is impeded by the lack of truly panoramic data. Sensitive mechanical measurements cover only a narrow cochlear region, mostly in the base. The global spatiotemporal pattern of vibrations along the cochlea cannot be inferred from such local measurements but is often extrapolated beyond the measurement spot under the assumption of scaling invariance. Auditory nerve responses give an alternative window on the entire cochlea, but traditional techniques do not allow recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 32 publications
9
54
3
Order By: Relevance
“…2. It reproduces panoramic measurements of cochlear wave propagation compiled from the phase of single nerve-fiber responses in single cat ears [10,19]. These spatial phase profiles show sharp bends at a location just basal to the peak region of the wave, which connect the shallow basal end of the phase profile (fast propagation) to the steeper portion near the peak (slow propagation).…”
Section: Amplitude Gain Does Not Stem From Power Bain But From Wave supporting
confidence: 59%
“…2. It reproduces panoramic measurements of cochlear wave propagation compiled from the phase of single nerve-fiber responses in single cat ears [10,19]. These spatial phase profiles show sharp bends at a location just basal to the peak region of the wave, which connect the shallow basal end of the phase profile (fast propagation) to the steeper portion near the peak (slow propagation).…”
Section: Amplitude Gain Does Not Stem From Power Bain But From Wave supporting
confidence: 59%
“…The deceleration produces a densification (focusing) of the energy that creates the peaking. This approach was motivated by neural data revealing a steep deceleration of cochlear waves near their peak (5,11). Rather than building an elaborate biophysical model, the aim was to find the simplest possible fluid waveguide exhibiting steep deceleration and peaking.…”
mentioning
confidence: 99%
“…In mammals, it has been shown that the phase curves were concave upward for CFG1 kHz and downward above (van der Heijden and Joris 2006;Temchin et al 2011;Versteegh et al 2011). As shown in Figure 10B, the concavity is related to the sign of the IF slope: A positive slope yields an upward concavity.…”
Section: Phase and Delaymentioning
confidence: 88%